Analisis Pelayanan Customer Service pada Kepuasan Konsumen dalam Perspektif Etika Bisnis Islam di LAZNAS Nurul Hayat Surabaya - Fayza Karunia Asadanie; Anwar, Moch. Khoirul (Universitas Negeri Surabaya, 2022)
Customer servce in a company and institutions especially those engaged in the service sector, has the function of providing good service so as to create satisfaction in consumers, by paying attention to ethics. The purpose of this study is to determine how the implementation of customer service on consumer satisfaction in the perspective of Islamic business ethics at LAZNAS Nurul Hayat Surabaya. This research used a descriptive qualitative using purposive sampling methods. This research has subject to be studied, namely internal and external, where the internal subjects are managers and staff customer service of LAZNAS Nurul Hayat Surabaya, and external subjects are consumers of LAZNAS Nurul Hayat Surabaya. The results of this study can be known that the implementation of customer service services in creating satisfaction in consumers has applied the general dimension of service, namely tangibles, responsivess, reliability, assurance, and emphaty. In addition, the implementation of customer service services in creating satisfaction in consumers has applied the principles of Islamic Business Ethics, namely the principle of unity, the principle of equilibrium, the principle of free will, the principle of responsibility, and the principle of benevolence.